Late Preceramic Forager–Herders from the Copacabana Peninsula in the Titicaca Basin of Bolivia: A Bioarchaeological Analysis. (6th October 2016) - Juengst, S. L.; Chávez, S. J.; Hutchinson, D. L.; Chávez, S. R.
Abstract: The Titicaca Basin of Peru and Bolivia has been occupied by humans for millennia and was home to one of the first major state societies in the Andes. Many foundations of state power, however, developed much earlier, during the Late Preceramic/Terminal Archaic Period (3000 – 1500 BC), when people initially began herding, marking territories, and creating new metallurgy technology. We present a skeletal analysis of 14 individuals dating between 3000 and 1500 BC from Muruqullu, an archaeological site on the Copacabana Peninsula of Bolivia. These are the first Preceramic burials documented for the peninsula and contribute to the relatively small sample of Preceramic bodies from the Andean highlands more broadly. From this sample, we suggest that highland foragers and early herders suffered little nutritional stress and had limited violent interactions, perhaps related to a relatively mobile lifestyle and utilisation of lake resources. Copyright © 2016 John Wiley & Sons, Ltd.